Agricultural Investment Data Analysis (AIDA) - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The Agricultural Investment Data Analysis (AIDA) tool is embedded in IFPRI’s Rural Investment and Analysis (RIAPA) modeling system. The integrated AIDA-RIAPA framework is used to analyze the economywide impacts of investments in the agri-food system (AFS) and help inform the design and prioritization of policies and investments given their impacts on development outcomes, such as economic growth, job creation, poverty reduction, or dietary improvements. Whereas AIDA is used to translate new investments in, say, irrigation, extension, or rural roads into changes in productivity, a recursive-dynamic Computable General Equilibrium (CGE) model, which sits at the core of the RIAPA system, measures the direct and indirect (spillover) effects of those investments on the rest of the economy. For example, investments in extension not only increase farm productivity of those receiving extension visits, but also create new jobs and income opportunities in downstream nonagricultural sectors, such as food processing, trading, and transport. This has welfare implications for households and individuals, which are analyzed using a series of microsimulation add-on modules also embedded in RIAPA.